Automated Vertical Hydroponic Farming - Seni, Sonia; Audah, Lukman (Evolution in Electrical and Electronic Engineering, 2020)
In the era of globalization, by producing our own food would lessen the food waste also save earth. Hydroponics farming is technique to grow a plants via a medium without the use of soil but nutrient solution or inorganic nutrients is involves. While vertical farming is where the plant is planted in stacked manners. Therefore this project are combination of both methods with the touch of technology. The process of taking care of the plant is reduced by using Blynk app to control and monitor the farming system. Thus, less interaction from human are requires. This project is an Automated Vertical Hydroponic Farming that would save energy and time consume for the consumer. Therefore, the aim of this project is to make an automated system that can monitor and control the required variable such as nutrients, water, light, and ambience to grow a type of Chinese cabbage name Pak Choy by using Float and Drain technique applied. The system is equipped with real-time mode for the consumer to monitored and control the farming system via smartphone. Hence, this project have been tested for the functionality of the sensors used in the prototype. Result of this study shows Automated Vertical Hydroponic Farming able to monitor growth of Pak Choi plants in aspect of humidity, temperature, grow light and nutrition levels.